2020
DOI: 10.11591/ijeecs.v17.i1.pp78-85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of fault location on distribution network using PSCAD and DIgSILENT power factory by using matching approaches

Abstract: This paper presents the comparative study between PSCAD and DIgSILENT in order to detect fault location on underground distribution network. If a fault occurs in the distribution network, it will generate the voltage dips and over current. It is possible to record the signal output in the primary substation. However, for the research purpose, some of the researcher may use different simulation program. The simulation program may have different performance to generate voltage and current signal when fault simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A technological process distinctive feature of modern hot-rolled metal production is its characteristic of being energy-intensive production which is accompanied by voltage dips resulting from powerful shock loads when the strip enters the stand. The issues of power quality indicators as well as voltage dips in the power supply network of metallurgical enterprises were being worked at by such scientific researches as [28]- [37]. The authors named above take up the factors that affecting the electricity quality both in a modern industrial enterprise conditions and within metallurgical production.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…A technological process distinctive feature of modern hot-rolled metal production is its characteristic of being energy-intensive production which is accompanied by voltage dips resulting from powerful shock loads when the strip enters the stand. The issues of power quality indicators as well as voltage dips in the power supply network of metallurgical enterprises were being worked at by such scientific researches as [28]- [37]. The authors named above take up the factors that affecting the electricity quality both in a modern industrial enterprise conditions and within metallurgical production.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Figures 5, 6, and 7 depict the MSE of PMU placement. The MSE is calculated as (11). The objective of LS-SVR in this study is to determine the accuracy of PMU placement based on MSE.…”
Section: Msementioning
confidence: 99%
“…Based on this research, the result shows that this paper was obtained the acceptable accuracy. By using matching approach, Awalin et al [11] was compare the accuracy by using different simulation tools namely, digilent and power system computer aided design (PSCAD) simulation program. From this study it is found that digsilent has a higher level of accuracy compared to PSCAD if the location of the disturbance using a matching approach.…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis is on detecting, identifying voltage dips [6], [7], and developing strategies for advanced control with protection systems of the wind turbine conversion chain, in order to satisfy the constraint of remaining connected during a voltage dip [3], [8]. Several [6], [9], [10]. However some methods allow only some voltage dips classification [6].…”
Section: Introductionmentioning
confidence: 99%